2005
DOI: 10.1196/annals.1313.007
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Molecular Redundancy in Autoimmune Inflammation in the Context of CD44 Deficiency

Abstract: Molecular redundancy refers to the ability of genes to back up damaged genes or gene loss. Although this term is widely discussed in many scientific circles, the process is still ill-defined, as shown by reviewing examples from the literature. Exploring the collagen-induced arthritis model in the context of CD44 knockout mice, we suggest a mechanistic explanation for molecular redundancy that depends neither on upregulation of the compensating molecule nor on structural similarity between the original molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…This study was undertaken to understand the mechanistic basis of the discrepancy between the effects of CD44 deficiency and anti-CD44 treatment on leukocyte recruitment in experimentally induced inflammatory arthritis, a disease in which most of the conflicting results have been reported. 8,10,15,31,32 We have found that the initial phases of leukocyte recruitment (rolling and adhesion) in the inflamed synovial vessels of mice are altered when CD44 is absent. The increased propensity of CD44 KO leukocytes to roll rather than adhere in this model is in line with previous reports, 19,20 although at present it is unclear to what extent the lack of HA recognition contributes to this alteration of leukocyte behavior in CD44 KO mice.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This study was undertaken to understand the mechanistic basis of the discrepancy between the effects of CD44 deficiency and anti-CD44 treatment on leukocyte recruitment in experimentally induced inflammatory arthritis, a disease in which most of the conflicting results have been reported. 8,10,15,31,32 We have found that the initial phases of leukocyte recruitment (rolling and adhesion) in the inflamed synovial vessels of mice are altered when CD44 is absent. The increased propensity of CD44 KO leukocytes to roll rather than adhere in this model is in line with previous reports, 19,20 although at present it is unclear to what extent the lack of HA recognition contributes to this alteration of leukocyte behavior in CD44 KO mice.…”
Section: Discussionmentioning
confidence: 96%
“…This was not exactly the case, however. For example, CD44 KO mice of the DBA/1 background showed moderate resistance 15 or no resistance 10 to collagen-induced arthritis, yet administration of CD44-specific mAbs to wild-type (WT) DBA/1 mice resulted in a prompt resolution of joint inflammation. 8,10 To understand the mechanistic basis of this discrepancy, we sought to determine by intravital video microscopy (IVM) how leukocyte recruitment (rolling/adhesion) in the blood vessels of inflamed joints was affected by CD44 deficiency vs anti-CD44 treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, mice incapable of forming HA–HC complexes, or treated with an anti-CD44 antibody, are more resistant to arthritis than wild-type littermates (196198). By contrast, in a proteoglycan-induced arthritis model, mice deficient in CD44 only exhibit moderate to no resistance (199, 200). HA complexes containing TSG-6 and IαI accumulate to high levels at inflammatory sites and may support CD44-mediated leukocyte rolling and adhesion, while potentially having anti-inflammatory effects (69, 155, 201).…”
Section: Evidence For In Vivo Importance Of Ha Fragmentsmentioning
confidence: 99%